2020
DOI: 10.1155/2020/2130341
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bionic Pit Structure on Friction and Sealing Performance of Reciprocating Plunger

Abstract: A new kind of pit-shaped bionic plunger proposes to reduce the frictional resistance of the reciprocating plunger and improve its sealing performance. According to the dorsal pore of earthworm, the bionic pit structure with different parameters designed and processed. The friction resistance test, observation test, and finite element analysis carried out. The results show that the bionic pit structure can improve the lubrication condition of the plunger surface and reduce the frictional resistance with a maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Etsion found a variety of surface textures that can significantly improve the performance of friction pairs [18,19]. These surface structures mainly include pit structures [20,21], groove structures [22][23][24][25][26] and other structures [27][28][29][30]. The pit structure includes circular pits, oval pits and square pits [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Etsion found a variety of surface textures that can significantly improve the performance of friction pairs [18,19]. These surface structures mainly include pit structures [20,21], groove structures [22][23][24][25][26] and other structures [27][28][29][30]. The pit structure includes circular pits, oval pits and square pits [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…As inspired by this, the bionic nonsmooth surface effect has been applied to various occasions, such as bearings, piston rings, mechanical seals, and cutting tools in relative motion, to improve the tribological properties, especially to reduce the friction of mechanical parts. Gao et al [16] proposed a novel pitshaped bionic plunger inspired by the dorsal pore of the earthworm. Through friction resistance test and finite element analysis, it has shown that the bionic structure can significantly improve the lubrication condition of the plunger surface with a maximum drag reduction rate of 14.32%.…”
Section: Introductionmentioning
confidence: 99%